A Critical Discourse Analysis on “Indonesia’s Jurassic Park-Inspired Tourist Attraction Worries Komodo Dragon Fans” News - Emanuel Rivaldo Saputra Gampur; Putu Nur Ayomi; Putu Devi Maharani (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
The news article is a powerful type of discourse that is often used to influence others and a medium where people can use its power over society. News is a media platform for sharing information. However, due to the journalist’s background, news can be unfair in delivering the topic. Therefore, critical discourse analysis plays a vital role in examining the true meaning of the news article. One of the current issues regarding Indonesian tourism is the development of Komodo Island. This study aims to analyze how news article from foreign media portray this issue by analyzing how the discourse structure and ideology is organized in the text by applying the theory of discourse structure, such as text structure, social cognition, and social context. The data source for this study was an ABC.com news article with the headline “Indonesia’s Jurassic Park-Inspired Tourist Attraction Worries Komodo Dragon Fans.” This study used a descriptive qualitative method with documentation, observation, and note-taking techniques. This study finds out that text structure is divided into the macrostructure, superstructure (five sub-topics), and microstructure consisting of semantic (background, details, goals, presupposition, numerical), syntactical (sentence form, pronouns, coherence), and rhetoric (brackets, dash, letter type, images, quotation mark). Social cognition includes role schemes, event schemes, and person schemes.